2018
DOI: 10.3126/jcmsn.v14i2.19324
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation using Orthopantomograph and Willems method in Chitwan population: an original study

Abstract: Background: Utilization of age estimation has increased manifold in recent years. Various methods available for age estimation before the complete dentition has erupted and matured till the root closure stage include Nolla’s stages, Demirijan”s method, modified Demirijan’s method by Willems, Haavikko’s method. So, in this study we have tested that on Chitwan population of Nepal.Materials and methods: 60 patients between the ages 6-16 were selected and digital orthopantomographs of each of the patients was take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…41 In a study done in a small population of Nepalese children also found Willems method to underestimate the dental age. 42 But another study though Based on the result of the current study, Demirjian's 7-teeth method has been found to be more applicable than Willems method in selected Nepalese children population.…”
Section: Resultsmentioning
confidence: 63%
“…41 In a study done in a small population of Nepalese children also found Willems method to underestimate the dental age. 42 But another study though Based on the result of the current study, Demirjian's 7-teeth method has been found to be more applicable than Willems method in selected Nepalese children population.…”
Section: Resultsmentioning
confidence: 63%
“…41 In a study done in a small population of Nepalese children also found Willems method to underestimate the dental age. 42 But another study though underestimated the dental age by Willems method, had performed better as compared to Demirjian with both the techniques exhibiting excellent correlation with chronological age in both the genders. 25 The present study also demonstrated strong positive association of chronological with dental age (DA and WA) for both the genders.…”
Section: Resultsmentioning
confidence: 91%
“…Comparably, a study done in a small population of Nepalese children also found Willems method to underestimate the dental age. 18 Another study done in Nepal using Demirjian and Willems techniques also showed underestimated dental age by Willems method. 19 Similarly, studies by Willems method have showed significant underestimation 2,28 and some studies have showed overestimation.…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, in a few studies done in selected Nepalese children population where Demirjian, Willems and Nollas methods have been used separately or in combined form have also found to underestimate the age. 14,[16][17][18][19] The application of the Demirjian, Willems and Nolla methods in the same design has been carried out only in four studies. 2,27,32,38 Maber et al, 32 Hegde S et al 38…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation